Controlling effect of saline sedimentary environment on enrichment and exploitation of shale gas and oil in lacustrine basin - Songbai Wu; Zhongxiang Zhao (SN Applied Sciences, 2022)
Article Highlights Under the same climate conditions, the salinity of continental lacustrine basin is mainly affected by the surrounding drainage system. The salinity of continental lacustrine basin affects the mineral composition and laminar of shale, which control the properties of shale.